2012
DOI: 10.1097/rlu.0b013e3182335f9b
|View full text |Cite
|
Sign up to set email alerts
|

F-18 FDG PET/CT for Detecting Bone and Bone Marrow Involvement in Sarcoidosis Patients

Abstract: More than one-third of PET/CT-positive sarcoidosis patients had osseous abnormalities on PET/CT. The majority of these lesions (94%) could not be detected on low-dose CT. No single localization of preference was found. These preliminary results stress the value of PET/CT imaging in the assessment of bone/bone marrow involvement in sarcoidosis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 15 publications
3
46
0
Order By: Relevance
“…Such an increased diagnostic yield closely corresponds to the results of Teirstein et al, who found occult sites on 18 F-FDG PET in 15% of patients that went undetected clinically or by conventional radiography and MDCT (22). An even higher prevalence (34%) of bone and bone marrow involvement undetected on CT has been reported (26). The additional information provided by 18 F-FDG PET/CT is likely to influence clinical management.…”
Section: Discussionsupporting
confidence: 67%
“…Such an increased diagnostic yield closely corresponds to the results of Teirstein et al, who found occult sites on 18 F-FDG PET in 15% of patients that went undetected clinically or by conventional radiography and MDCT (22). An even higher prevalence (34%) of bone and bone marrow involvement undetected on CT has been reported (26). The additional information provided by 18 F-FDG PET/CT is likely to influence clinical management.…”
Section: Discussionsupporting
confidence: 67%
“…Positron emission tomography/computed tomography (PET/CT) imaging can be useful in the assessment of bone involvement in sarcoidosis patients. ( 31 ) …”
Section: Osseous Sarcoidosismentioning
confidence: 99%
“…It is currently unclear how often asymptomatic sarcoid bone lesions are incidentally detected in PET imaging [7]. Mostard et al [10] showed that more than one-third (32/94) of PET-CT-positive sarcoidosis patients had osseous abnormalities on PET-CT; however, there was no single preference of bone localization. Another interesting finding in their study is that corresponding CT lesions were identified in only 2 of the 32 patients with PET-detected bone abnormalities.…”
Section: Discussionmentioning
confidence: 98%